Public Services Bureaucracy Performance (Case Study Of Public Relation, Information And Public Communications in South Sulawesi Province): English, Indonesia - Parebba, Zainal Arifin; Hamsina; Ahmad, Badu; Anugrah, Edhib Harits (Universitas Airlangga, 2022)
Abstract The research entitled Public Service Bureaucracy Performance (Case Study Of Public Information and Public Communications) has several problems, including the lack of maximum services provided by the communication and informatics department in terms of services to the community. Basically, research on the quality of public services is important to do, because the community as customer service has not been satisfied in terms of time, cost and quality of service that has been provided. For this reason, this research is aimed at improving the quality of public services, especially those carried out in the field of Public Relations, Information and Public Communication, South Sulawesi Province. To see the phenomenon above, the writer uses the Dwiyanto theory with five indicators, namely productivity, service quality, responsiveness, responsibility and accountability. In this study, the author uses a qualitative method with a case study approach. The results found are still rampant, sometimes admin operators are less responsive and sometimes operators do not understand that the report will be forwarded to the relevant agency. And the time of service is also not certain. Abstrak Penelitian yang berjudul Kinerja Birokrasi Pelayanan Publik (Studi Kasus Informasi Publik dan Komunikasi Publik) memiliki beberapa permasalahan, antara lain kurang maksimalnya pelayanan yang diberikan oleh dinas komunikasi dan informatika dalam hal pelayanan kepada masyarakat. Pada dasarnya penelitian tentang kualitas pelayanan publik penting untuk dilakukan, karena masyarakat sebagai pelanggan pelayanan belum puas dalam hal waktu, biaya dan kualitas pelayanan yang telah diberikan. Untuk itu penelitian ini ditujukan untuk meningkatkan kualitas pelayanan publik khususnya yang dilaksanakan di bidang Humas, Informasi dan Komunikasi Publik Provinsi Sulawesi Selatan. Untuk melihat fenomena diatas, penulis menggunakan teori Dwiyanto dengan lima indikator yaitu produktivitas, kualitas pelayanan, daya tanggap, tanggung jawab dan akuntabilitas. Dalam penelitian ini, penulis menggunakan metode kualitatif dengan pendekatan studi kasus. Hasil yang ditemukan masih merajalela, terkadang admin operator kurang tanggap dan terkadang operator tidak mengerti bahwa laporan akan diteruskan ke instansi terkait. Dan waktu pelayanannya juga tidak pasti.